2020
DOI: 10.14434/ijdl.v11i2.27010
|View full text |Cite
|
Sign up to set email alerts
|

Drive Student Success: Designing a MakerBus to Bring Standard-Based Making and Technology Activities into K-12 Schools

Abstract: Designing a mobile makerspace, the MakerBus, originated from our goal of bringing maker education to all students in K-12, thus empowering students to believe they could create things and make social changes. This design case was guided by human-centered design principles and rapid prototyping instructional design model. In this paper, we elaborated on the process of designing the MakerBus, highlight major design decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…The research methods used in the selected papers included, (a) matched survey responses (i.e., repeated measures) (Andrews et al, 2021), (b) inductive video coding where codes were extracted from the data (Hatzigianni et al, 2021), (c) a mixed-method strategy comprising the systematic integration of qualitative and quantitative research (Juškevičienė et al, 2021), and (iv) a Likert scale-based pre-and post-questionnaire specifically designed for activities conducted in makerspaces. The Likert scale-based pre-and post-questionnaires are the most common methods used in the literature (Andrews et al, 2021;Couch et al, 2019;Jin et al, 2020;Saorín et al, 2017;Selznick, 2019;Taheri et al, 2020). It can be concluded that each of the above creativity assessment methods can be selected based on the creativity aspect under assessment and the type of data available (e.g., the abreaction test).…”
Section: Creativity and Assessment Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The research methods used in the selected papers included, (a) matched survey responses (i.e., repeated measures) (Andrews et al, 2021), (b) inductive video coding where codes were extracted from the data (Hatzigianni et al, 2021), (c) a mixed-method strategy comprising the systematic integration of qualitative and quantitative research (Juškevičienė et al, 2021), and (iv) a Likert scale-based pre-and post-questionnaire specifically designed for activities conducted in makerspaces. The Likert scale-based pre-and post-questionnaires are the most common methods used in the literature (Andrews et al, 2021;Couch et al, 2019;Jin et al, 2020;Saorín et al, 2017;Selznick, 2019;Taheri et al, 2020). It can be concluded that each of the above creativity assessment methods can be selected based on the creativity aspect under assessment and the type of data available (e.g., the abreaction test).…”
Section: Creativity and Assessment Methodsmentioning
confidence: 99%
“…(i) Implementing an adequately designed maker-based pedagogy that joyfully engages students in learning. This allows students to fully express themselves without fear of failure, allowing them to experiment, explore, and learn fundamental skills, such as lateral thinking, problem-solving, creativity, and innovation (Beyers, 2010;Jin et al, 2020). (ii) Student-centered project-based learning, where students create prototypes that are meaningful to them.…”
Section: How Do the Identified Aspects Of Makerspaces Foster Creativity?mentioning
confidence: 99%
“…The obtained outcomes indicated a significant increase in EF abilities" were made because of integrating the artistic tasks. Jin, Martin, Stephens, and Carrier (2020) carried out research, the aim of which was to use a Maker Bus to provide visual arts to the neighborhood's schools and community. To provide children the opportunity to create, researchers extensively rebuilt a bus that has been equipped with several art-making supplies.…”
Section: Visual-art Education and Academic Achievementsmentioning
confidence: 99%
“…To provide children the opportunity to create, researchers extensively rebuilt a bus that has been equipped with several art-making supplies. According to Jin, Martin, Stephens, and Carrier (2020), the main goal of the investigation was that kids utilize creativity and intelligence for designing or constructing things. The study's findings revealed that the Maker Bus gave kids many opportunities to acquire and create via the visual arts while utilizing several skills and materials.…”
Section: Visual-art Education and Academic Achievementsmentioning
confidence: 99%